Validating a TPACK Instrument in the Moroccan Context: A Four-Factor Model for Preservice Mathematics and Sciences Teachers - Ahmichane, Jamal; Jhilal, Abdellatif; Hadder, Youness; El Mallahi, Mostafa (International Journal of Environment, Engineering and Education, 2025)
Numerous theoretical frameworks have been proposed to guide research on teachers’ technology integration. Among them, the Technological Pedagogical Content Knowledge (TPACK) framework has recently emerged as a prominent conceptual model, emphasizing the composite knowledge teachers require to integrate technology into teaching effectively. This study aims to investigate the development of TPACK among primary school pre-service teachers (PSTs) specializing in mathematics and science within the Moroccan context. 403 PSTs in postgraduate teacher preparation programs participated in this research and completed the TPACK survey. Their responses were analyzed using exploratory and confirmatory factor analyses (EFA and CFA). The survey instrument, consisting of 32 items, was categorized into five major subgroups corresponding to core TPACK components. Findings revealed that pre-service teachers faced difficulty distinguishing and self-reporting their technological pedagogical knowledge. The CFA results demonstrated that the constructs of TPACK, content knowledge, pedagogical knowledge, and technological knowledge were valid and reliable indicators of pre-service teachers’ competencies in this setting, despite the relatively weak convergent validity observed in the pedagogical knowledge component. The study offers implications and recommendations for future research and teacher education practices. In particular, the validated TPACK survey provides a potential diagnostic tool for assessing novice teachers’ knowledge profiles and identifying areas for professional growth. These insights enhance technology integration courses and strengthen teachers’ instructional efficacy across North African educational contexts.